Effect of high temperature thermomechanical treatment on the tendency of low-activation 12% Cr ferritic-martensitic steel EK-181 to low-temperature embrittlement - Polekhina, Nadezhda A.; Linnik, Valeria V.; Almaeva, Kseniya V.; Litovchenko, Igor Yu; Tyumentsev, Alexander N.; Moskvichev, Evgeny N.; Chernov, Vyacheslav M.; Leontyeva-Smirnova, M. V.; Degtyarev, Nikolay A.; Moroz, Kirill A. (Russian physics journal)
The effect of high-temperature thermomechanical treatment (HTMT) with deformation in the austenitic region on the regularities of low-temperature embrittlement of low-activation 12% chromium ferritic-martensitic steel EK-181 is investigated in comparison with traditional heat treatment (THT) during dynamic tests on impact toughness and static tests on uniaxial tension in the range from -196 to 20 degrees C. It is found out that HTMT increases both the tensile strength properties of steel and its impact toughness. At the same time, the temperature of its ductile-brittle transition does not practically change relative to the THT. It is observed that the features of steel microstructure after HTMT, the formation of delaminations (during fracture of Charpy-type specimens) in the planes parallel to the plane of hot rolling, have a positive effect on its impact toughness.